Pemanfaatan ReactJS dan Protokol MQTT untuk Visualisasi Sinyal Lampu dan Notifikasi secara Waktu Nyata pada Sistem Pemonitor APILL di Kota Pekanbaru - Ardianto Wibowo; Muhammad Mahrus Zain (Jurnal Komputer Terapan, 2021)
The majority of signalized intersections in Pekanbaru city are still regulated by analog controllers. The main problem that occurs with this condition is the occurrence of long traffic jams if there is damage to the traffic light controller. Thus, the Pekanbaru City Transportation Department cannot act immediately once a problem occurs. Related to these problems, an integrated system has been developed that functions to manage and monitor traffic light conditions in real time. This research is focused on discussing the use of ReactJS and MQTT. ReactJS is used to display traffic light light signal data and provide real time notifications into a web browser. Meanwhile, MQTT is used as a medium to manage data communication between the detection module installed on the traffic light controller in the field to the Back-End server. This data is then displayed to the web browser via React JS. With the solution in this research, it is hoped that the Pekanbaru City Transportation Office can find out the problems of traffic light lamps in the field quickly, so that they can immediately take the relevant actions needed.